Helicobacter pylori down-regulates expression of human ß-defensin 1 in the gastric mucosa in a type IV secretion dependent fashion - Patel, S.R.; Smith, K.; Letley, D.P.; Cook, K.W.; Memon, A.A.; Ingram, R.J.M.; Staples, E.; Backert, S.; Zaltoun, A.M.; Atherton, J.C.; Robinson, K. (Wiley, 2013)
Helicobacter pylori establishes a chronic lifelong infection in the human gastric mucosa, which may lead to peptic ulcer disease or gastric adenocarcinoma. The human beta-defensins (hβDs) are antimicrobial peptides, hβD1 being constitutively expressed in the human stomach. We hypothesized that H. pylori may persist, in part, by downregulating gastric hβD1 expression. We measured hβD1 and hβD2 expression in vivo in relation to the presence, density and severity of H. pylori infection, investigated differential effects of H. pylori virulence factors, and studied underlying signalling mechanisms in vitro. Significantly lower hβD1 and higher hβD2 mRNA and protein concentrations were present in gastric biopsies from infected patients. Those patients with higher-level bacterial colonization and inflammation had significantly lower hβD1 expression, but there were no differences in hβD2. H. pylori infection of human gastric epithelial cell lines also downregulated hβD1. Using wild-type strains and isogenic mutants, we showed that a functional cag pathogenicity island-encoded type IV secretion system induced this downregulation. Treatment with chemical inhibitors or siRNA revealed that H. pylori usurped NF-κB signalling to modulate hβD1 expression. These data indicate that H. pylori downregulates hβD1 expression via NF-κB signalling, and suggest that this may promote bacterial survival and persistence in the gastric niche.